Utilizarea „Psaltirii” în „Didahiile” lui Antim Ivireanul - Gianina Maria-Cristina Picioruş (Revista de Istorie și Teorie Literară)
This paper shows the way in which Antim Ivireanul, creating his Didaches, inserts excerpts from The Psalter into the discourse. We pointed out that he used to investigate previous Romanian translations of the psalms along with Greek and Latin originals (Septuaginta and Vulgata). It can be observed, from our research, that Antim preferred the translations into Romanian from the Bucharest Bible of 1688 and those made by Dosoftei for the Psalter of 1680. But our analysis of the didaches proves that Antim did not only consult his sources, but he was also correcting them or he was giving them a form which he considered suitable for the oral rhetoric of his time. In this way, Antim greatly contributed for the Romanian literary language to evolve into its modern form that we know today.